2013
DOI: 10.1021/ja404107p
|View full text |Cite
|
Sign up to set email alerts
|

Magnetocaloric Effect in AlFe2B2: Toward Magnetic Refrigerants from Earth-Abundant Elements

Abstract: AlFe2B2 was prepared by two alternative synthetic routes, arc melting and synthesis from Ga flux. In the layered crystal structure, infinite chains of B atoms are connected by Fe atoms into two-dimensional [Fe2B2] slabs that alternate with layers of Al atoms. As expected from the theoretical analysis of electronic band structure, the compound exhibits itinerant ferromagnetism, with the ordering temperature of 307 K. The measurement of magnetocaloric effect (MCE) as a function of applied magnetic field reveals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
174
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(188 citation statements)
references
References 38 publications
13
174
1
Order By: Relevance
“…For magnetic refrigeration near room temperature, several suitable materials are being studied in detail, including (Mn,Fe) 2 (P,Si), 7,8 La(Fe,Si) 13 and its hydrides, 9 and Heusler compounds. 10,11 These systems are comprised of Earth-abundant, inexpensive elements and combine large ∆S M and ∆T ad , with low hysteresis, high mechanical and chemical stability, and good thermal properties. Despite great progress within these systems, discovery of new magnetocalorics with desirable properties is still important.…”
Section: Introductionmentioning
confidence: 99%
“…For magnetic refrigeration near room temperature, several suitable materials are being studied in detail, including (Mn,Fe) 2 (P,Si), 7,8 La(Fe,Si) 13 and its hydrides, 9 and Heusler compounds. 10,11 These systems are comprised of Earth-abundant, inexpensive elements and combine large ∆S M and ∆T ad , with low hysteresis, high mechanical and chemical stability, and good thermal properties. Despite great progress within these systems, discovery of new magnetocalorics with desirable properties is still important.…”
Section: Introductionmentioning
confidence: 99%
“…In the aluminium layer the atoms occupy the 2a-position and in the (Fe 2 B 2 )-slabs iron and boron occupy the 4j and 4i positions, respectively. In previous studies, magnetic measurements and Mössbauer spectroscopy have shown that AlFe 2 B 2 is a ferromagnetic material with reported values of T c varying between 282-320 K and saturation magnetic moments ranging between 0.95 and 1.25 µ B /Fe-atom [8][9][10]. The magnetic entropy change has been reported to -4.1 and -7.7 J/K kg at an applied magnetic field of 1600 and 4000 kA/m, respectively [9].…”
Section: Introductionmentioning
confidence: 99%
“…This materials challenge has proven to be formidable; in addition to difficulties with materials fabrication, mechanical integrity and corrosion issues during cycling, many magnetothermal materials under consideration today contain rare, toxic or strategically-limited elements: these materials include Gd, Gd 5 (GeSi) 4 , FeRh, MnAs, FeMnAsP and (La((FeCo)Si(H)) 13 [4]- [7]. Against this backdrop the recent report of a room-temperature magnetocaloric effect in the ferromagnetic compound AlFe 2 B 2 is of interest [8]. This intermetallic compound is comprised entirely of non-critical, easily accessible, stable and easily recyclable elements.…”
Section: Introductionmentioning
confidence: 99%